FLIPPING THE CLASSROOM: ENHANCING LEARNING THROUGH ACTIVE ENGAGEMENT AND PERSONALIZED INSTRUCTION - Sultonova Malika (Journal of new century innovations, 2024)
Abstract: The traditional model of classroom instruction, characterized by lectures delivered during class time and homework assignments completed independently outside of class, has been increasingly challenged by innovative approaches aimed at promoting active learning and student engagement. One such approach is the flipped classroom model, where traditional lecture content is delivered outside of class through pre-recorded videos or readings, allowing class time to be dedicated to interactive activities, discussions, and personalized instruction. This thesis explores the concept of flipping the classroom, its theoretical foundations, implementation strategies, and its impact on student learning outcomes, engagement, and satisfaction.